Development of IWMI-AREO Collaborative Research Program to Improve Land and Water Management in Iran - Qureshi, Asad Sarwar (2004)
Irrigated agriculture and, consequently, water have always played an important role in the economic development of Iran and is likely to continue as such in the future. Since agriculture is the major user of water, therefore sustainability of agriculture depends on the timely and adequate availability of water. The increasing pressures of population and industrialization have already placed greater demands on water, with an everincreasing number and intensity of local and regional conflicts over its availability and use. Iran will face severe water shortages in the 21st century. The gap between demand and supply of water is increasing. The extended drought during recent years exacerbated the problem. Therefore, the need for further development of new resources, adoption of water-conservation measures and judicious use of water is being stressed at all forums. This paper will provide a comprehensive review of the present water resources of Iran, challenges faced by the irrigated agriculture and strategies to overcome these problems to ensure sustainability of irrigated agriculture. This paper will also suggest possible research areas for future cooperation between IWMI and Iran in the field of land and water management. It is envisaged that discussions at the workshop will help in refining these ideas and develop partnerships and linkages among various national research institutions and IWMI to develop a comprehensive program for the years to come.